2014
DOI: 10.1177/0194599814557614
|View full text |Cite
|
Sign up to set email alerts
|

Test Battery of Cranial Nerves VII and VIII for Assessing Herpes Zoster Oticus

Abstract: Grading of the facial nerve alone fails to predict the outcome of facial paresis in patients with HZO mainly because it overlooks the involvement of CN VIII. Alternatively, a combined test battery of CNs VII and VIII may serve as a strong predictor for facial nerve recovery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…19,20 To verify the concept, another 43-year-old male patient with herpes zoster oticus, manifested by eruption, facial paresis, and hearing loss on the right ear, was adopted for comparison. 16 Serological assay confirmed the reactivation of varicella-zoster virus, and MR imaging demonstrated a linear gadolinium-enhanced lesion in the IAC of the right ear ( Figure 3B). Although recovery of facial nerve function was identified, hearing loss on the right ear remained unchanged despite treatment.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…19,20 To verify the concept, another 43-year-old male patient with herpes zoster oticus, manifested by eruption, facial paresis, and hearing loss on the right ear, was adopted for comparison. 16 Serological assay confirmed the reactivation of varicella-zoster virus, and MR imaging demonstrated a linear gadolinium-enhanced lesion in the IAC of the right ear ( Figure 3B). Although recovery of facial nerve function was identified, hearing loss on the right ear remained unchanged despite treatment.…”
Section: Discussionmentioning
confidence: 90%
“…An inner ear test battery including audiometry, cVEMP, oVEMP, and caloric tests, revealed abnormal responses on the lesion ear (Figures 1 and 2), indicating that the respective inner ear end organs, that is, cochlea, saccule, utricle, and semicircular canals were substantially affected. 16 Since vascular insufficiency and autoimmune disease are less relevant in young adults, viral infection may play a dominant role for precipitating SSHL in young adults after dental procedure. Serological assay identified increased varicella-zoster virus IgM antibody titers, further confirmed that SSHL following dental procedure in this young adult is caused by reactivation of the varicellazoster virus.…”
Section: Discussionmentioning
confidence: 99%
“…Vestibular disorders in RHS have been reported more frequently, in 50-80% of cases [13,17]. The different means of investigation (i.e., only caloric tests or a larger number of exams) may justify this wide range.…”
Section: Resultsmentioning
confidence: 99%
“…The different means of investigation (i.e., only caloric tests or a larger number of exams) may justify this wide range. Huang et al reported that in a sample of 20 subjects, only 40% showed abnormal calorics, while 65% presented pathological cervical vestibular-evoked myogenic potentials (cVEMPs) [17]. Conversely, the authors found that involvement of the eighth nerve was prognostic for poor recovery of facial palsy [18].…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, the functional repair of peripheral nerves and pain relief can be effectively promoted. 30 Ultrasound-guided puncture has been proven to be a simple, safe, economic, and less painful microinvasive technique. With ultrasound guidance, doctors can more clearly observe the local structure of the target, the puncture pathway, and the real-time diffusion of local anesthetics, thus greatly improving the success rate of nerve block and reducing complications.…”
Section: Discussionmentioning
confidence: 99%